(untitled) (World Economics and Finance Bulletin, 2026)
The article examines the issues of disclosure of estimated liabilities in financial statements. The three-level (mandatory, recommended and additional) disclosure concept developed by the author increases the transparency of financial reporting compared to ancient approaches. The concept was developed for enterprises in the field of ICT in accordance with the requirements of the BHXS 37 standard.